Economic burden of private tutoring at higher secondary level in Pakistan: An analysis through Hurder and Linear regression model - Parveen, Khalida; Alghamdi, Abdulelah A.; Javed, Iqbal; Din, Imad U (Frontiers in Psychology, 2022)
Economic burden of private supplementary tutoring is increasing around the world. Demand for private supplementary tutoring, contributing factors and their effects are investigated in the study. For this purpose, data was collected through questionnaire, multi-stage non-probability technique was used. Hurder model was used to find the factors affecting demand for private supplementary tutoring at higher secondary level. Linear regression model was used to find the economic burden of family and factors affecting the demand for private tutoring. The findings showed that several factors have significant effect on demand for private supplementary tutoring, and some of them significantly impacting on economic burden. The study recommends regulating the market of shadow education because of differentiated tuition fee in different tuition centers to cut down the burden of private tutoring for households.